Features of the influence of the factor of internal aggression on the socialization of athletes after the completion of the career - Skrygin, S. V.; Galochkin, P.V.; Yurchenko, A. L.; Anurov, V. L. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the level of aggressiveness of athletes of various specializations who have completed their careers as a factor in their asocialization.